Electrocortical evidence for the time course processes of attentional bias toward infant faces. (23rd March 2019) - Li, Bingbing; Li, Xu; Xu, Mengsi; Diao, Liuting; Zhang, Dajun
Highlights: Attentional orientation toward infant vs. adult faces was reflected by an early N2pc. Attentional orientation toward infant faces was not influenced by emotional valence. Attentional orientation toward infant faces was not sustained in all face pair types. An inverted late N2pc followed the initial orientation toward happy infant faces. Abstract: Previous behavioral studies have demonstrated that adults show initial orientation toward neutral infant faces compared to neutral adult faces. However, it is unclear whether the initial orientation toward infant faces is sustained and whether attentional bias toward infant faces exists under different emotional valences. In the present study, event-related potentials were recorded while nulliparous women performed a dot-probe task to identify the time course processes involved in attentional bias toward infant faces. Three face pair types were used in the task; each face pair type contained one infant facial expression (happy, neutral, or sad) and one adult facial expression with the same emotional valence. An early N2pc was observed for each face pair type, which suggests that there was initial orientation toward infant faces irrespective of emotional valence. The absence of sustained posterior contralateral negativity in all face pair types indicated that attentional orientation was not sustained at the later stage of attentional selection. In addition, an inverted late N2pc was observed for the happy face pairs and may reflect a "happy superiority effect" in attentional selection processing.